The University and the White, Rural Male - Melissa E. Whiting (Journal of Research in Rural Education, 1999)
Howley (1997) argues that rural education has its own legitimate place in educational research. He questions the idea that rural schools must mirror their cosmopolitan counterparts in order to achieve educational excellence. In short, he suggests that institutions and their affiliated educational researchers need to rethink their own positions on the issues connected to rural education and its students. The following is a result ofa year-long study on the interaction between a rural student and hisfirst-year composition professor. The struggles ofthis nontraditional university student, along with the idea ofaudience, language forms, and adaptation to a new culture, suggest that the burden ofchange is not the student's alone. The university itselfmust learn to recognize, acknowledge, and work within all students' potential for academic success.